2000
DOI: 10.1292/jvms.62.1241
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Intrauterine Horn Insemination of Fresh Semen in Cats.

Abstract: ABSTRACT. The sperm count required were investigated to obtain a conception rate of 80% by unilateral intrauterine insemination (UIUI) of fresh semen in cats. The conception rates obtained by insemination before and after ovulation were also examined. Thirty-six female cats aged 1-7 years were used in the experiments, and the number of experimental cases was 44. Seven male cats aged 2-12 years from which semen could be collected by the artificial vagina method were used. In artificial insemination, 100 iu × 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 8 publications
2
36
4
Order By: Relevance
“…High pregnancy rates (67-75%) were achieved in ferrets when anesthesia and insemination were conducted at either 24 h post-hCG ($6 h before anticipated ovulation) or the time of hCG administration ($30 h before ovulation). Interestingly, these ferrets were in natural estrus, similar to the cats in the study conducted by Tsutsui et al [66] that demonstrated an 80% pregnancy success. These findings further support the concept that eCG-induced estrus might affect follicular sensitivity to the ovulatory process.…”
Section: Developing Assisted Reproduction Via Studying Ferret 'Models'supporting
confidence: 75%
See 2 more Smart Citations
“…High pregnancy rates (67-75%) were achieved in ferrets when anesthesia and insemination were conducted at either 24 h post-hCG ($6 h before anticipated ovulation) or the time of hCG administration ($30 h before ovulation). Interestingly, these ferrets were in natural estrus, similar to the cats in the study conducted by Tsutsui et al [66] that demonstrated an 80% pregnancy success. These findings further support the concept that eCG-induced estrus might affect follicular sensitivity to the ovulatory process.…”
Section: Developing Assisted Reproduction Via Studying Ferret 'Models'supporting
confidence: 75%
“…It was recognized that two semen collection procedures may be required to achieve this high cellular density for a single insemination [65]. In contrast, Tsutsui et al [66,67] achieved a conception rate of 80% in the cat by intrauterine insemination (by laparotomy) but using only 8 Â 10 6 fresh sperm into a single uterine horn. This relationship between insemination site and number of sperm required for conception also has been observed in the dog [68].…”
Section: Site Of Inseminationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the semen qualities after thawing were not reported, and thus, we could not evaluate the extender used in their study. Therefore, we prepared frozen feline semen using egg yolk fructose citric acid (EYT-FC) [6,7], which we use as an extender for fresh feline semen, and egg yolk sodium citrate (EYC), which is an extender of bovine semen [4], and compared the semen quality after thawing and the conception rate obtained by UIUI. To ensure uniform conditions for the freezing method, a cell freezer (Cell Freezer R204, England) was used.…”
mentioning
confidence: 99%
“…To ensure uniform conditions for the freezing method, a cell freezer (Cell Freezer R204, England) was used. For AI, UIUI was performed, as reported [7] for insemination of fresh semen, and we investigated the fertilization of ova in the non-inseminated uterine horn by the inseminated sperms. Because a higher conception rate was previously obtained by insemination before ovulation than insemination after ovulation, AI was performed 15 or 20 hr after hCG administration, a time point predicted to be prior to ovulation [7].…”
mentioning
confidence: 99%